A queueing system with heterogeneous impatient customers and consumable additional items - Baek, Janghyun; Dudina, Olga; Kim, Chesoong (Zielona Góra: Uniwersytet Zielonogórski)
A single-server queueing system with a marked Markovian arrival process of heterogeneous customers is considered. Type-1 customers have limited preemptive priority over type-2 customers. There is an infinite buffer for type-2 customers and no buffer for type-1 customers. There is also a finite buffer (stock) for consumable additional items (semi-products, half-stocks, etc.) which arrive according to the Markovian arrival process. Service of a customer requires a fixed number of consumable additional items depending on the type of the customer. The service time has a phase-type distribution depending on the type of the customer.
Keywords: marked Markovian arrival process; consumable additional items; phase-type distribution; impatient customers